Facile access to a heterocyclic, sp3-rich chemical scaffold via a tandem condensation/intramolecular nitrone–alkene [3+2] cycloaddition strategy1. Issue 64 (18th August 2015) - Rawling, M. J.; Storr, T. E.; Bawazir, W. A.; Cully, S. J.; Lewis, W.; Makki, M. S. I. T.; Strutt, I. R.; Jones, G.; Hamza, D.; Stockman, R. A.
<x xml:space="preserve">Abstract</x> A heterocyclic, sp3-rich chemical scaffold was synthesised in just 6 steps via a highly regio- and diastereo-selective tandem nitrone formation/intramolecular nitrone–alkene [3+2] cycloaddition reaction.